2022
DOI: 10.1101/2022.05.31.494105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Volumetric bioluminescence imaging of cellular dynamics with deep learning based light-field reconstruction

Abstract: The application of genetically encoded fluorophores for microscopy has afforded one of the biggest revolutions in the biosciences. Bioluminescence microscopy is an appealing alternative to fluorescence microscopy, because it does not depend on external illumination, and consequently does neither produce spurious background autofluorescence, nor perturb intrinsically photosensitive processes in living cells and animals. The low quantum yield of known luciferases, however, limit the acquisition of high signal-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For future work, these techniques can be useful for further analysis in more complex systems such as glutamatergic neurons, zebrafish epithelial cell organization, volumetric calcium dynamics in the body wall muscle and ensemble of neurons in freely moving animals. 15 Also, spatiotemporal resolution can be improved by training with real experimental data for the suppression of errors in the images due to misalignment in the setup or optical aberrations. Additionally, preprocessing steps might allow to improve the input quality to boost the 3D reconstruction performance.…”
Section: Single Exposure Light Field Imaging For Volumetric Biolumine...mentioning
confidence: 99%
See 1 more Smart Citation
“…For future work, these techniques can be useful for further analysis in more complex systems such as glutamatergic neurons, zebrafish epithelial cell organization, volumetric calcium dynamics in the body wall muscle and ensemble of neurons in freely moving animals. 15 Also, spatiotemporal resolution can be improved by training with real experimental data for the suppression of errors in the images due to misalignment in the setup or optical aberrations. Additionally, preprocessing steps might allow to improve the input quality to boost the 3D reconstruction performance.…”
Section: Single Exposure Light Field Imaging For Volumetric Biolumine...mentioning
confidence: 99%
“…Therefore, in order to acquire high SNR data, this approach commonly demands long exposure times in the order of seconds or even tens of seconds, which limits the applications to slow biological dynamics and gene expression analyses. 11 Convolutional neural networks have been widely applied in microscopy research and have shown to outperform classical algorithms in different tasks such as segmentation, 12 denoising, [13][14][15] 3D reconstruction methods, 15,16 and superresolution. 17 The main reason for this is that neural networks take advantage of the knowledge available about the data.…”
Section: Introductionmentioning
confidence: 99%